Etnomedisin Param (Kuning) sebagai Obat Tradisional di Desa Bunuraya Kabupaten Karo - Nensi Grafika Br Sinuraya; Ashar Hasairin (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This study aims to document the use of plants used in making param (kuning) as a traditional medicine of the Karo Tribe in Bunuraya Village so that the knowledge of the community is not lost with the progress of the times. The location of the research was carried out in Bunuraya Village, Tigapanah District, Karo Regency. The methods used in this study are qualitative and quantitative descriptive methods, using semi-structured interview methods and participatory observation. Research result show that the number of plants used as raw material for param (kuning) is 22 species covering 13 families. The most widely used percentage of plant families is the Zingiberaceae family with a percentage of 22.72%. The most widely used organ is the rhizome organ with a percentage of 22.72%. The most widely used plant habitus is herbs with a percentage of 63.63%. The origin of the most plants obtained is cultivation with a percentage of 54.54%. The Karo Tribe people believe that the use of plants in making param (kuning) as a traditional medicine can treat various diseases, improve health and maintain health. The important cultural value in this study is divided into 4 categories, namely very high, high, medium and low. Very high values consist of 5 species with a value of 100, high values consist of 11 species with a value (66-99), medium values consist of 5 species with a value (24-40) and low values consist of 1 species with a value of 12. The use value of param (kuning) as the highest traditional medicine consists of 16 benefits with a value of 0.72.